Analisis Makna dan Ketahanan Budaya Seni Tari Endel Di Desa Slarang Lor - Andriarsih, Lyswidia; Khamid, Achmad Farchan; Mumtazi, Safir Firdaus; Tsaqiba, Saffanah; Alisa, Salsabila Febri; Amalia, Shieva Amanah (Profetik: Jurnal Pengabdian Masyarakat, 2024)
In every region there are always things that are characteristic of that region. Slarang Lor is famous for its characteristic, namely the Endel Dance, because the creator of the Endel Dance comes from Slarang Lor Village. Many people from various groups want to learn and practice Endel Dance, such as elementary school, middle school, high school children and others. Endel Dance is included in the type of traditional folk dance, because it was created by the local community in Slarang Lor Village. The endel dance was created from generation to generation from ancient ancestors, but in Slarang Lor we are not really familiar with the meaning and movements of the endel dance itself. Therefore, with the hope that the Endel mask dance can be better known and can be learned about the meaning, movements and how to maintain the Endel dance so that it does not disappear as a characteristic of the area.